Characterization and surface activity of soluble sulfonated butanone formaldehyde superplasticizer for cement - Sultana, S; Yeasmin, Z; Ahmed, S; Nur, HP; Samaddar, PR (Bangladesh Journal of Scientific and Industrial Research, 2016)
Water soluble sulfonated butanone formaldehyde (SBF) polycondensate superplasticizer was prepared according to a conventional method. UV-Vis, IR and TGA analyses were performed to analyze the target compound. The surface activity was evaluated. It showed a little surface activity with respect to water as the surface tension decreased very little with increasing the concentration of SBF. Thus there results indicate that SBF behaves like a typical polycondensate superplasticizer such as sulfonated acetone formaldehyde (SAF). Bangladesh J. Sci. Ind. Res. 51(2), 155-158, 2016